Challenging Gender Binaries in A ‘Journey to Honor’: A Feminist Critique of Performativity in Mulan (2020) Movie - Kusen, Felicia Jessica; Noah, Abimanyu; Setiawan, Steven Febryan; Silaen, Gwyneth Lillian (Jurnal Pendidikan Makarios, 2024)
This study examines the portrayal of gender roles of the characters and the social expectations in ‘Mulan,’ (2020) the live-action movie, using the feminist theory of gender performativity by Butler, J. (1990). The research focuses on how Mulan’s character challenges traditional gender roles in Chinese society, the significance of "chi" as a metaphor for inner strength and its gendered portrayal, and the societal consequences of defying gender expectations. By applying a qualitative approach, the study explores key aspects such as female stereotypes, empowerment, and cultural symbols within the movie, while connecting them to feminist theory. The research reveals that 1) Mulan’s character actively subverts the gender binary of masculinity versus femininity by assuming roles traditionally reserved for men, thereby challenging stereotypes about female weakness. 2) The metaphor of "chi" is analyzed as a representation of inner strength, with Mulan’s mastery of it breaking gendered associations of power with masculinity. 3) The movie highlights the societal risks women face when defying gender norms, as well as the rewards of embracing individuality and agency. The movie offers a nuanced depiction of gender roles, blending Confucian values with feminist ideals. Mulan’s journey not only represents female empowerment but also blurs the lines between traditional masculine and feminine traits, ultimately questioning the fixedness of gender identity. This study aims to contribute to feminist discussions in literary analysis through movies as media and offer insight into how globalized interpretations of cultural narratives can reflect evolving perspectives on gender equality.